Evaluation of a Two-Phase Implementation of a Tier-2 (Small Group) Reading Intervention for Young Low-Progress Readers. Issue 2 (29th October 2014) - Buckingham, Jennifer; Wheldall, Kevin; Beaman-Wheldall, Robyn
Abstract : In a response to intervention (RtI) model, reading is taught in increasingly intensive tiers of instruction. The aim of the study was to examine the efficacy of a Tier-2 (small group) literacy intervention for young struggling readers. This article focuses on the second phase of a randomised control trial involving 14 students in kindergarten as participants. In Phase 1 of the randomised control trial, the experimental group (E1) received the intervention for 1 hour, 4 days per week, for 3 school terms. The control group received regular classroom instruction. Large and statistically significant mean differences between groups were evident after 3 terms on 2 of 4 measures — the Martin and Pratt Nonword Reading Test and the Burt Reading Test, which measure phonological recoding and single word reading, respectively. Very large effect sizes were found. In Phase 2, the original control group received the intervention in the same way (E2). Testing at the end of Phase 2 confirmed the intervention's large effect on phonological recoding, but the results for the 3 other tests showed no acceleration in the Phase 2 experimental group (E2). This study evaluates the efficacy of the trialled intervention, adds to the research literature on Tier-2 interventions for young struggling readers, and yields practical implications for schools that offer literacy interventions without a strong RtI framework.